Collapse of corrugated metal culvert in Northern Sardinia: analysis and numerical simulations. (2016) - Giresini, Linda; Puppio, Mario L.; Sassu, Mauro
The paper illustrates the possible causes of collapse of a Corrugated Metal Culvert (CMC), occurred in Northern Sardinia after an extreme rainfall event in 2013. The possible causes of collapse are related to the conditions before and during the rainfall. Erosion and corrosion phenomena, which caused material decay and an improper water flow, have been discussed. Numerical analyses were performed to identify buckling multipliers with a finite element model simulating the effect of combined erosion and corrosion. The analysis showed a greater sensitivity in terms of buckling resistance when the soil erosion is concentrated in the lower portion of the culvert rather than in the lateral one.